Epidemiology of clinically significant migraine in Israel: a retrospective database study - A. Shifrin; E. Domany; M. Tirosh; D. Davidovici; S. Vinker; I. Forschner; A. Israel (The Journal of Headache and Pain)
Abstract Background Epidemiological studies on migraine are valuable for tracking disease trends, identifying risk factors, and informing treatment strategies. This study assessed the prevalence and annual incidence of clinically significant migraine in Israel from 2017 to 2022, with analyses stratified by age, sex, socioeconomic status, and district. Additionally, we compared relevant characteristics between adult migraine and non-migraine members of Leumit Healthcare Services (LHS), a national health provider in Israel. Methods This retrospective study used LHS electronic health records to evaluate migraine prevalence and annual incidence from 2017 to 2022 among adult LHS members. Clinically significant migraine patients were identified using stringent criteria, including repeated diagnostic codes for migraine, confirmation by a neurologist, or the use of migraine-specific therapies. Each migraine patient was matched 1:1 with a control individual of similar age, sex, socioeconomic status, and ethnic background. Results The prevalence of clinically significant migraine increased from 4.5% in 2017 to 5.2% in 2022, with significantly higher rates in women compared to men (8% vs. 2.4% in 2022). The mean age of migraine patients was 46.8 years in 2022. The annual incidence of migraine in 2022 was 43 per 10,000 individuals over 18, with approximately 75% of new cases occurring in women, with a mean age of 36.5 years. The annual incidence of migraine slightly decreased over the period. Approximately two-thirds of new patients were diagnosed by neurologists, with only 19% diagnosed by family physicians. Compared to a matched control population, migraine patients showed a higher prevalence of low body mass index (BMI) and higher diastolic blood pressure (BP). Additionally, distinct differences in laboratory findings were observed among migraine patients, notably lower glucose and hemoglobin A1c levels, lower rate of microalbuminuria, with higher hemoglobin, which may be associated with migraine pathophysiology. Conclusion This study provides a detailed epidemiological and clinical profile of patients with clinically significant migraine in LHS from 2017 to 2022. Notable trends include higher rates of migraine among patients with lower BMI, higher diastolic BP, lower glucose, and higher hemoglobin, suggesting potential modifiable risk factors.